PHYSICIANS’ COMPETENCE IN TERMINATING CPR IN CARDIAC ARREST CASES AND FACTORS INFLUENCING THIS TERMINATION - KHALID , MA; NAWADAT , Q; KAUSAR , U (Biological and Clinical Sciences Research Journal, 2023)
The study aimed to evaluate the competence and knowledge of the cardiac arrest team regarding CPR termination and the factors that influence this termination. A cross-sectional study was conducted in the Department of Cardiology, Shifa International Hospital April 2022-April 2023). A total of 300 cardiac arrest team members (physicians and nurses) designated to perform advanced cardiac life support were included in the study. Questionnaires were distributed among the participants inquiring about their competence and knowledge about terminating CPR. Of 100 physicians, 40 (40%) were not competent enough to decide on CPR termination. 10% of physicians and 5% of nurses agreed to be aware of the ERC termination guidelines, and only one physician and one nurse could state the contents. The majority of the participants reported terminating resuscitation if the patient was older than 90 years, absent direct pupillary reflex, true asystole, and witnessed cardiac arrest without bystander resuscitation in 10 minutes. Based on the results, the physicians and nurses in Pakistan are not competent in decision-making regarding CPR termination in cardiac arrest patients and are unaware of the factors and guidelines while making such decisions.